Analisis Bauran Pemasaran di Kampung Budaya Sindangbarang, Bogor - Sarah Iasya; Nur Fitriyani; Chairrun Nisha Nur Rochman (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2022)
This research discusses Marketing Mix (7p) at Kampung Budaya Sindangbarang. Determination of location based on potential to develop a tourist attraction that allegedly unpopular to many people because of weak marketing, also there is no research on marketing in this destination. The purpose of this study is to analyze the application of marketing mix in Kampung Budaya Sindangbarang according the perception of tourists. This study is using quantitative descriptive approach. The quantitative approach is used to describe statistics analysis. The data collection method used in this research is primary data and secondary data. The number of samples was determined using Slovin theory, and 100 samples were obtained by sample determination using quota sampling. Questioner result is measured by using nominal scale, interval scale and likert scale. The tools used to process data and obtaining the result of calculation is Microsoft Excel and SPSS. The result of this research is indicate that the implementation of the marketing mix at Kampung Budaya Sindangbarang has been done well, but there are still certain things that must be improved so that tourists increase. The conclusion of this research is the characteristics of tourist and the success of the marketing mix in Kampung Budaya Sindangbarang are obtained with an average value of 3.50, also the most influential and the weakest marketing mix element is discovered.